Aerosol assisted chemical vapor deposition of magnesium orthotitanate (Mg 2 TiO 4 ) films from a trinuclear molecular precursor - Ehsan, M.A.; McKee, V.; Naeem, R.; Hakeem, A.S.; Mazhar, M. (Elsevier, 2017)
Present work demonstrates the synthesis of a novel heterobimetallic complex [Mg2TiO(TFA)6(THF)2(H2O)] (1) (where TFA = trifluoroacetato and THF = tetrahydrofuran), formed from the chemical interaction of magnesium (II) acetate tetrahydrate with titanium (IV) isopropoxide and trifluoroacetic acid in THF solution. Complex (1) adequately characterized through attenuated total reflection infrared spectroscopy, single-crystal X-ray diffraction and thermogravimetric analysis was implemented as single source molecular precursor in the aerosol assisted chemical vapor deposition. The deposition of magnesium orthotitanate (Mg2TiO4) ceramic films on fluorine doped tin oxide coated conducting glass substrate was observed at various temperatures of 500, 550 and 600 °C. Film characterization techniques including; X-ray powder diffraction, scanning electron microscopy, energy dispersive X-ray and X-ray photoelectron spectroscopy divulge the fabrication of phase pure spherical shaped Mg2TiO4 architectures with precise stoichiometry and high purity.